Discovery of novel vitamin D receptor interacting proteins that modulate 1,25-dihydroxyvitamin D(3) signaling - Marshall, Pamela A. (2012)
The nuclear vitamin D receptor (VDR) modulates gene transcription in 1,25-dihydroxyvitamin D(3) (1,25D) target tissues such as kidney, intestine, and bone. VDR is also expressed in heart, and 1,25D deficiency may play a role in the acceleration of cardiovascular disease. Employing a yeast two-hybrid system and a human heart library, using both a 1,25D-independent and 1,25D-dependent screen, we discovered six candidate VDR interacting proteins (VIPs). These novel VIPs include CXXC5, FASTK, NR4A1, TPM2, MYL3 and XIRP1. Mammalian two-hybrid assays as well as GST pull-downs were used to confirm VIP-VDR interaction, and the combination of these two assays reveals that CXXC5, XIRP1, FASTK and NR4A1 interactions with VDR may be modulated by 1,25D. The functional effects of these VIPs on 1,25D-mediated gene expression were explored in transcriptional assays employing three separate and distinct 1,25D-responsive element (VDRE)-driven luciferase reporter genes in transfected Caco-2 and HEK-293 cells, and in a C2C12 myoblast line. FASTK and TPM2 activated expression in all cell line and promoter contexts, while CXXC5 and XIRP1 exhibited differing effects depending on the cell line and promoter employed, suggesting promoter and cell-specific effects of these unique VIPs on VDR signaling. Further evaluation of the interaction between CXXC5 and VDR revealed that CXXC5 acts in a dose-dependent manner to stimulate VDR-mediated transcription on select VDREs. Identification of novel heart VIPs and their influence on VDR activity may increase our understanding of how vitamin D impacts cardiac physiology and may facilitate development of VDR/VIP drug analogs to combat heart disease.